Emmanuel Macron: Anatomy of a Transgression - Tournois, Laurent (Eximia, 2024)
Among current Western heads of state, Emmanuel Macron is undoubtedly the most unique. Although he was only 39 years old when he was elected for the first time and 44 years old for the second time, he had never previously held an elective office. However, he shares with two of his predecessors, François Mitterrand and Jacques Chirac, the fact of having held two mandates. This path is in itself atypical, not to say ‘disruptive’ compared to that of all the presidents who preceded him. This term is also the communication marker not only of his victorious 2017 presidential campaign but above all a key element of his political orientation. However, if he did, at first, ‘disrupt’ the political landscape in France, this momentum very quickly died down to such an extent that the political character he embodies has crystallized hopes, disappointments and then anger and even hatred. Such reactions lead to question the real contribution of this disruption. Until now, these questions have only been partially addressed, leaving room for the implementation of an original approach which consists in postulating that this disruption actually masks a transgression. Through the prism of transgression, this paper aims to decipher this (false) disruption as his journey from 2016 as a candidate until his second term has been illustrated by a variety of behavioral forms and lexical expressions. I approach these aspects in the form of critical narrative writing, which is based on concrete details, spoken words, speeches, interviews, and other texts.